Analisis Perubahan Penutup Lahan Di Sub Das Kamp Wolker Kota Jayapura Tahun 2013 Dan 2023 Menggunakan Citra Landsat 8 - Hamokwarong, Yehuda; Abrauw , Rudolf Doni (Jurnal Sosial Teknologi, 2025)
The aim of this research is to determine (1) the spatial distribution of land cover in the Wolker Camp Sub-watershed, Jayapura City in 2013 and 2023; (2) dynamics of changes in land cover in the Wolker Camp Sub-watershed, Jayapura City in 2013 and 2023. This research uses quantitative descriptive research methods with remote sensing techniques through Landsat-8 LDCM image analysis and land cover classification using supervised classification maximum likelihood for images from the 2013 and 2023 clips. The results of this research are Landsat 8 OLI/TIRS image processing including radiometric correction, geometric correction, image sharpening, digital classification using the Maximum Likelihood supervised classification method on ArcGIS software and carrying out accuracy tests using the confusion matrix. Furthermore, the results of the overall accuracy and kappa statistics of the Maximum Likelihood classification based on the sample and confusion matrix show that the Landsat-8 LDCM image data has a kappa accuracy of 94.218% with a sample size of 240 samples. The land cover in the Wolker Camp Sub-watershed consists of five classes, namely Thicket, Forest, Fields/Moorlands, Settlements and Open Land and the class that experienced quite large changes or decreases was Forest, around 15.89 Ha/year, while the change in Open Land was other land cover is estimated at around 2.49 Ha/year. Apart from that, there has been an increase in the area of the Settlement class, which in 2013 was around 286 Ha to 384 Ha in 2023.